(untitled) - Mullins, Olivia (Hoboken, New Jersey, 2016)
There's no better way to learn about the world around us than to test how things work—and that's exactly what this book guides kids to do. Featuring easily achievable projects your youngster can complete using simple household items, Experimenting with Science is designed to appeal to your little one's inner Einstein—and helps them have a whole lot of fun in the process.
Keywords: Khoa học,Science; Thử nghiệm,Experiments